(المشترك اللفظي من لفظ "ضرب" في القرآن الكريم (دراسة تحليلية دلالية - Iswah Adriana; Suci Fitria (OKARA: Jurnal Bahasa dan Sastra, 2018)
This research article describes about musytarak words or homonym (ضرب) in the Qur’an, it means these words are continually spelled alike with their various shighat (condition) existed in different verses or letters in the Qur’an with their various meaning. This focus is related to the one of the linguistic fields namely semantics. This study is qualitative one, researcher used content analysis to analyze the data about musytarak words or homonym. The research revealed that there are some meanings of homonyms (ضرب) found in the different verses still relate between one meaning to another meaning, however, there are some homonyms that the meanings do not relate one another at all. This research article also outlines the forms of words and also why they have different meanings although they are spelled alike (homonym/ ضرب) in the Qur’an. By knowing the musytarak words or homonym in Qur’an, it is expected that readers, especially moslems understand more about the Qur’an.